An integrative taxonomic approach to describe Andricus pseudomultiplicatus sp. nov. and establish new synonymies in Andricus Hartig, 1840 (Hymenoptera: Cynipidae: Cynipini) - Sottile, Salvatore; Nicholls, James A.; Stone, Graham N.; Cerasa, Giuliano (Zootaxa, 2025)
An examination of type and non-type material deposited in various European scientific collections concludes that the sexual generation of Andricus truncicolus (Giraud, 1859), recently discovered through laboratory experiments and herein confirmed by molecular data, is synonymous with Andricus multiplicatus Giraud, 1859; the latter name becomes a junior synonym. We demonstrate that previously published phylogenetic analyses did not group these two taxa together due to morphological misidentification of the sexual form. We show that the mistakenly identified taxon is a species new to science, described herein as Andricus pseudomultiplicatus sp. nov. along with illustrations, diagnosis, host associations, distribution, biology and molecular data. We also provide multi-locus molecular evidence to support the previously published lifecycle closure and synonymisation of Andricus conificus (Hartig, 1843) and Andricus cydoniae Giraud, 1859.